Analisis Current Ratio, Quick Ratio, dan Cash Ratio pada PT. Nippon Indosari Corpindo Tbk - Nuraini Nuraini; Nurhayati (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the liquidity level of PT Nippon Indosari Corpindo Tbk through the measurement of Current Ratio, Quick Ratio, and Cash Ratio. The study employed a descriptive quantitative approach using secondary data obtained from the company's financial statements published by the Indonesia Stock Exchange (IDX). The sample consisted of the financial statements of PT Nippon Indosari Corpindo Tbk for the 2020–2024 period selected through purposive sampling. Data analysis was conducted using liquidity ratio analysis and a one-sample t-test with the assistance of SPSS version 22. The results indicate that the Current Ratio is lower than or equal to the 200% benchmark, indicating that the company's liquidity condition based on the Current Ratio is not yet satisfactory. Meanwhile, the Quick Ratio exceeds the 150% benchmark and the Cash Ratio exceeds the 50% benchmark, indicating good liquidity performance. These findings suggest that the company has a relatively strong ability to meet its short-term obligations, although improvements in current asset management are still needed to optimize the Current Ratio